EXPLORING PRE-SERVICE TEACHERS’ EXPERIENCES WITH PLOTAGON IN EFL DIGITAL STORYTELLING - Fazah Nadia; Aridah Aridah; Effendi Limbong; Istanti Hermagustiana; A.K. Amarullah (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
This research explores the experience of ten fifth-semester EFL pre-service teachers from Universitas Mulawarman who employed Plotagon to create digital storytelling projects in a Digital Literacy course. Adopting a qualitative research design, data were collected from participants' written reflections and examined thematically. The findings emphasize five broad themes: integration of local culture, in this case folklore from East Kalimantan, into EFL courseware; technological challenges and creative coping with additional tools; creativity and collaboration through cooperative production; attitudes towards usefulness and usability that impacted technology appropriation; and redefinition of learner and teacher roles as learners took on teller and media producer roles. These findings tell us that in spite of extensive use of culture as objects, greater digital literacy levels, and greater practice on the part of learners, the subjects were affected by the presence of limited functionality of Plotagon, faulty hardware, and inconsistent group participation, thereby requiring the necessity of having institutional backing as well as training. This study contributes to fresh understanding regarding the enabling of technology flexibility, cultural awareness, and learning autonomy through the use of digital storytelling tools like Plotagon in pre-service teacher education and illustrates not only their ability to produce language and digital literacy but also their ability to improve the competence of pre-service teachers in teaching innovative, forward thinking, and culture-sensitive.